The Effectiveness of the Mind Mapping in PjBL on the Learning Outcomes and the Creativity of Elementary School Students - Fortuna, Kurnia Perdana Dharma; Aeni, Kurotul (International Journal of Elementary Education, 2024)
The methods and models applied by teachers affect learning outcomes and student creativity. This research intends to analyze differences and effectiveness of mind mapping methods in the project-based learning model in terms of creativity and learning outcomes. The research method used is experimental research with a quasi-experimental design. The reseaech subjects were 41 students, 22 students in grade 4 A as a control group, and 19 students in grade 4 B as an experimental group. Data collection procedures in this research used test procedures and observation sheet assessment rubrics. The statistical tests used in this research include normality tests, homogeneity tests, t-tests, observation sheet tests, and N-Gain were assisted by SPPS for Windows version 25 and Microsoft Excel. The independent sample t-test yielded a significance value (sig.2-tailed) of 0.000, that is less than 0,05. This implies that H0 is disused while Ha is allowable. This suggests that there exists a major gap admist mind mapping approach used in the project-based learning paradigm and student learning outcomes. The N-Gain score for the experimental class was 0,64, while for the control class was 0,36. Both scores fell within the medium category. The N-Gain Percent for the experimental class was found to be effective, while for the control class, it was not. The data revealed that the average student creativity score for each indicator during the four meetings in the experimental class was higher than in the control class. Furthermore, the value of each N-gain score indicator at each meeting in the experimental class increased.